EFEKTIVITAS PROGRAM KELAS CATIN YANG DIIKUTI OLEH WARGA KELURAHAN PAKIS KOTA SURABAYA - Oktaviani, Diana; Priambodo, Bayu (Jurnal Progress Administrasi Publik, 2024)
The catin class program is a program launched by DP3APPKB Surabaya City which aims to reduce cases of stunting and problems in families. The Catin class is a form of training activity and provides guidelines for prospective brides and grooms before getting married. This program was launched because of cases in the city of Surabaya which showed that there were still many families who were not ready to create a harmonious family. Therefore, this research aims to analyze the effectiveness of implementing catin classes in household life for residents in Pakis Village, Surabaya City. The method used in this research uses a qualitative research method with a descriptive approach, researchers also make efforts by observation and interviews to collect data, information, and respondents' views. Data analysis techniques in this research include data reduction, data display, and drawing conclusions. The results of this research show that the Catin Class program is running effectively because it uses Edy Sutrisno's theory of effectiveness with research through five indicators starting from program understanding, right on target, on time, achievement of goals, and real change. It can be concluded from this research that the implementation is very effective because the Catin Class material is applied directly in daily life and provides benefits and new views for each individual.   Keywords: Effectiveness; Catin Class; Surabaya City